Monetary Transmission of Global Imbalances in Asian Countries - Lee, Il (IMF Working Papers; Working Paper ;, 2010)
The paper explores the linkages between the global and domestic monetary gaps, and estimates the effects of monetary gaps on output growth, inflation, and net saving rates using panel data for 20 Asian countries for 1980-2008. We find a significant pass-through of the global monetary gap to domestic monetary gaps, which in turn affect output growth and inflation, in individual emerging market and developing countries in Asia. Notably, we provide evidence that the global monetary condition is partly responsible for the current account surplus in Asia. We also draw implications for monetary policy coordination for global rebalancing.